1987
DOI: 10.1111/j.1749-6632.1987.tb23776.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Vitamin C in Blood Components by High‐Performance Liquid Chromatography

Abstract: The fact that platelets, PMN leukocytes, and MN leukocytes concentrate ascorbic acid suggests that vitamin C has an important role in their physiological functions. The question still remains as to which one of the cells best reflects vitamin C status. The ascorbic acid content of PMNs and platelets correlates positively with plasma concentration and supplementation with vitamin C, as shown in Evans et al. They also found that MN leukocytes, in contrast, do not show any such relationship; however, MN leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…These results are consistent with the known active accumulation of ascorbate by cells to concentrations many times more than in the extracellular space [18,65,66]. The ascorbate levels in human neutrophils and monocytes in vivo [16] are similar to the levels of ascorbate taken up by HL-60 and U937 cells, using our approach. Although the molar concentration of ascorbate is higher in the cells compared to the media, at 1 × 10 6 cell mL −1 there will be ≈50 -200 times more moles of ascorbate in the media than in the cells.…”
Section: Cellular Uptake Of Asch − Is Higher In U937 Cells Compared Tsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with the known active accumulation of ascorbate by cells to concentrations many times more than in the extracellular space [18,65,66]. The ascorbate levels in human neutrophils and monocytes in vivo [16] are similar to the levels of ascorbate taken up by HL-60 and U937 cells, using our approach. Although the molar concentration of ascorbate is higher in the cells compared to the media, at 1 × 10 6 cell mL −1 there will be ≈50 -200 times more moles of ascorbate in the media than in the cells.…”
Section: Cellular Uptake Of Asch − Is Higher In U937 Cells Compared Tsupporting
confidence: 89%
“…As a vitamin, it must be taken up from the diet; it is found in almost all tissues [16]. It's concentration in the blood of normal individuals varies from 5 to 90 μM [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is also a co-factor in the biosynthesis and post-translational modification of collagen due to interaction with proline hydroxylase [12,13], and has been demonstrated to affect immune function [14], platelet activation [15], prostaglandin synthesis [16] and the polyol pathway [3]. These observations suggest apossible close interrelationship between AA metabolism and pathways known to be influenced by the diabetic process.Although leucocytes act as a storage reservoir for ascorbic acid and thus are considered by some workers to reflect overall vitamin C status, leucocyte concentrations do not correlate well with intake [17], are technically more difficult to measure, and are subject to a variety of influences such as stress, surgery, tobacco smoking, and exercise [18]. In comparison, plasma and serum ascorbate levels have been shown to reflect metabolic turnover of the vitamin [19], respond more rapidly to supplementation [20], and are relatively simple and convenient to measure.…”
mentioning
confidence: 99%
“…Although leucocytes act as a storage reservoir for ascorbic acid and thus are considered by some workers to reflect overall vitamin C status, leucocyte concentrations do not correlate well with intake [17], are technically more difficult to measure, and are subject to a variety of influences such as stress, surgery, tobacco smoking, and exercise [18]. In comparison, plasma and serum ascorbate levels have been shown to reflect metabolic turnover of the vitamin [19], respond more rapidly to supplementation [20], and are relatively simple and convenient to measure.…”
mentioning
confidence: 99%
“…It has been suggested that increased free radicals and decline of antioxidant defense mechanisms induce diabetic micro-and macrovascular complications (1)(2)(3). Vitamin C is one of the major antioxidants and is detected in various blood components (4). However, measurements of vitamin C levels have shown inconsistent results, and the interpretation of vitamin C levels in diabetes as an antioxidant biomarker has not been clarified (5)(6)(7)(8).…”
mentioning
confidence: 99%